1992
DOI: 10.1139/p92-210
|View full text |Cite
|
Sign up to set email alerts
|

Composition et coefficients de transport des plasmas de matériaux plastiques (polymères)

Abstract: Composition at equilibrium, electrical and thermal conductivities, and dynamic viscosity coefficient are calculated for plasmas produced by vaporization of plastic materials (polymers) containing some percentage of carbon, hydrogen, oxygen, and nitrogen. Temperature and pressure ranges are 5000 – 30 000 K and 0.1–1 MPA. By indicating the role played by some particles on the characteristics of the discharge, this study has shown the influence of the nature of the material.[Journal translation]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
2
11
0
1
Order By: Relevance
“…The more significant the maximum λ R is, and the shorter the arc lifespan is. In addition, some others studies [6,9] have shown that more the percentage of atoms H is raised and more the form of λ(T) of the plasma is interesting. On figure 7 appear the evolutions of electrical conductivities (σ) of studied plasmas.…”
Section: Results and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The more significant the maximum λ R is, and the shorter the arc lifespan is. In addition, some others studies [6,9] have shown that more the percentage of atoms H is raised and more the form of λ(T) of the plasma is interesting. On figure 7 appear the evolutions of electrical conductivities (σ) of studied plasmas.…”
Section: Results and Analysesmentioning
confidence: 99%
“…Circuit breakers made object of numerous theoretical and experimental studies [1,2,3,4,5]. Other studies on the electrical arc have shown the influence of the insulator vapors [6,7,8,9], metals [4,10,11] and hydrogen [6,9] on the engendered plasmas characteristics. In this study, we are interested by hydrogen influence on plasma characteristics for electrical current breaking.…”
Section: Introductionmentioning
confidence: 99%
“…When the solid phase of carbon has not yet been formed the results are identical in the two cases. The concentrations between temperatures of 5000 and 10 000 K were given in our previous paper [15] and for temperatures higher than 10 000 K they have been given in various papers: PMMA in [1,6], PA6-6 in [1,5,6,11], PETP in [1,6], POM in [1,6] and PE in [1,4].…”
Section: Resultsmentioning
confidence: 99%
“…Il existe plusieurs méthodes pour la détermination de la composition chimique dans un plasma. A l'équilibre thermodynamique, lorsque l'on veut prendre en compte un grand nombre d'espèces chimiques, deux grandes familles de méthodes sont habituellement utilisées ; l'une est basée sur la loi d'action de masse [2,13,14] et l'autre sur la minimisation de l'énergie libre de Gibbs [3,6,15]. Dans ce travail nous avons utilisé la méthode de minimisation de l'énergie libre de Gibbs, car elle est très efficace et facile à mettre en oeuvre [3].…”
Section: Méthode De Calcul De La Composition Chimiqueunclassified